The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/ecc.12642
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment among prostate cancer patients: An overview of reviews

Abstract: To identify and clarify definitions and methods of measuring cancer‐related cognitive impairment among prostate cancer patients treated with androgen deprivation therapy (ADT) and to assess the incidence and prevalence of cognitive impairment. A systematic review of Medline, EMBASE, PubMed, PsycINFO and CINAHL up to December 2015 was undertaken to identify English‐language reviews. A total of 28 reviews were identified describing 20 primary studies. There were no studies of incidence. Reported prevalence rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
41
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 56 publications
(180 reference statements)
0
41
0
1
Order By: Relevance
“…The development of cognitive impairment in cancer patients is linked to various psychosocial or tumor-related factors [ 10 ]. However, there are no systematic assessment tools to predict the risk for CRCI complications in colon cancer patients after chemotherapy [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The development of cognitive impairment in cancer patients is linked to various psychosocial or tumor-related factors [ 10 ]. However, there are no systematic assessment tools to predict the risk for CRCI complications in colon cancer patients after chemotherapy [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cardiopulmonary fitness has traditionally been assessed before radical prostatectomy, as part of enhanced recovery pathways [5] or prior to prehabilitation [6]. It is well recognised that surgery can have a significant impact on catabolism and oxygen demand, and the length and extent of surgery is directly related to the risk of developing post-surgery complications [7].…”
Section: Introductionmentioning
confidence: 99%
“…There are androgen receptors in the brain and it is not surprising that withdrawal of testosterone has been linked to changes in verbal memory, visuospatial ability, and executive functions. A recent systematic review of the literature on cognitive effects in ADT found substantial variation in the rates reported and the magnitudes of effects because of heterogeneity in the definitions and measurement tools used [10]. The length of follow-up for all studies was limited and varied, with no study having longer than 12 mo of follow-up.…”
mentioning
confidence: 99%